Digital Cognitive Behavioral Therapy (dCBT) for insomnia: a State-of-the-Science review - Luik, A; Kyle, S; Espie, C (Springer, 2017)
Purpose of Review Over the past decade, digital solutions have been developed to support the dissemination of Cognitive Behavioral Therapy (CBT). In this paper, we review the evidence for and implications of digital CBT (dCBT) for insomnia. Recent Findings We propose three categories of dCBT, which differ in the amount of clinician time needed, level of automatization, costs, and scalability: dCBT as support, guided dCBT, and fully automated dCBT. Consistent evidence has been published on the effectiveness of dCBT to address insomnia disorder, in a variety of populations, with effects extending into well-being. Important gaps in the literature are identified around moderators and mediators of dCBT, costeffectiveness, and the implementation of dCBT. Summary The evidence base for dCBT is rapidly developing and already suggests that dCBT for insomnia is effective. However, further science and digital innovation is required to realize the full potential of dCBT and address important clinical questions.